Application of heart rate variability during blood pressure measurement in patients with somatic symptom disorder. (April 2020) - Huang, Wei-Lieh; Liou, Horng-Huei; Ouyang, Hsing; Liao, Shih-Cheng
Highlights: LF and RMSSD were associated with somatic symptoms in female and depression in male SSD patients, respectively. LF was helpful to detect the severe somatic symptoms in women with SSD. RMSSD and PSI were helpful to detect the clinically meaningful depression in men with SSD. Abstract: Objective: This study wants to test whether the heart rate variability (HRV) analysis using sphygmomanometers can effectively reflect the physical and emotional distress of somatic symptom disorder (SSD) cases and assist in further health management. Methods: This study includes 66 female SSD cases and 32 male SSD cases. All cases received a 200-second blood pressure (BP) measurement, after which the numerical figure for the heart rate was obtained from the BP signal for HRV analysis. All cases also filled out Patient Health Questionnaire-15 (PHQ-15), Beck Depression Inventory-II (BDI-II), Beck Anxiety Inventory (BAI) to understand the extent of their somatic distress, depression, and anxiety. The relationship between psychological conditions and HRV indicators are examined statistically. Receiver operating characteristic (ROC) curve analysis was used to understand whether HRV indicators can assist in the determination of psychosomatic problems. Results: Considering all and female SSD cases, low-frequency power (LF) and PHQ-15 in the HRV index have the most significant correlations. In male SSD cases, root mean square of successive NN interval differences (RMSSD) and BDI-II have the highest correlations. The results of ROC curve analysis indicate that LF is useful to judge the severity of female SSD cases, while RMSSD has reference value in determining whether male patients of SSD cases have depression or not. In addition, physical stress index (PSI) can also help determine the degree of depression in male SSD cases. Conclusion: The use of BP in HRV analysis can help in the monitoring of somatic distress and depression issues in SSD cases. LF, RMSSD, PSI are potential physiological indicators.